THE USE OF ASSISTIVE TECHNOLOGY FOR SPECIAL NEED STUDENTS - Lailatus Sa’adah (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2020)
This study focused on the use of assistive technology in language teaching. Moreover, the aim of this study was to analyze the students’ perception toward the use of assistive technology in English listening skill. The participant of this study was all of the students of special school (SMA Luar Biasa) consist of disable and blind. The research method used was a descriptive qualitative design. In addition, the interview is used to know the students’ perception toward the use of assistive technology and then observation was applied to confirm the data from process of teaching listening using assistive technology.